Simple method for the concentration of influenza virus from allantoic fluid on microporous filters. - Goyal, S M (1980)
Membrane filter adsorption-elution is an efficient method for concentration and partial purification of several types of viruses from various aqueous solutions. For efficient virus adsorption to negatively charged filters, the sample is adjusted to pH 3.5 and trivalent salts are added before filtration. Since influenza virus is sensitive to extremes in pH, it cannot be concentrated by ordinary filters. Zeta Plus filters, which have a net positive charge of up to 5 or 6, were evaluated for the concentration of influenza virus from infectious allantoic fluids. Influenza virus efficiently adsorbed to Zeta Plus filters at pH 6, and addition of salts was not necessary. Adsorbed virus was eluted in a small volume of 2% bovine serum albumin plus 1 M NaCl at pH 10. By this procedure, viruses in 100 ml of allantoic fluid were concentrated to a final volume of 8 ml, with an average recovery efficiency of 71.0%.